Sistem Informasi Akuntansi Pendapatan dan Pengeluaran Kas Pada SMK Bhinneka Patebon Menggunakan Metode Cash Basis - Kamto Sudibyo, sukemi; Nur Asriyah, Fitri; Ihsanil Huda, Haris; Miftahurrohman; Munifah (Jurnal Ilmiah Sistem Informasi, 2022)
At SMK Bhinneka Patebon in the process of recording cash income and disbursements data and reports are still done manually using notes and books, there is often a buildup of transactions that have not been recorded. This resulted in the problem of making reports less fast and accurate for making reports because it took a longer time. The Cash Revenue and Expenditure Accounting Information System at the Bhinneka Patebon Vocational School uses the Cash Basis Method to facilitate the Bhinneka Patebon Vocational School in the process of managing cash income and disbursement data in making reports that are faster, more precise and accurate. By using the Cash Income and Expenditure Accounting Information System at the Bhinneka Patebon Vocational School using the Cash Basis Method, it also has the following benefits: (1) It can be seen what cash income and expenditure transactions are needed quickly and accurately. (2) Produce precise and accurate financial reports. (3) The system is used by the school principal as a means of accountability to the Foundation for later use as a consideration for decision making by the Foundation